The financial structure of Singapore - Monetary Authority of Singapore (Singapore : Economics Dept., Monetary Authority of Singapore, 1980)
The objective of this publication is to provide information on the structural changes in the financial sector and new financial activities which have developed. The publication contains a brief description of the financial institutions and markets , their structure, functions and recent developments.
osc 30/01/2019
Loans
Keywords: Finance